Abdominal tuberculosis: a surgical emergency - Bali, Rajandeep Singh; Jain, Rahul; Zahoor, Yawar; Mittal, Ankul (International Journal of Research in Medical Sciences, 2017)
Background: To study and assess the clinico-pathologic profile, intra-operative findings, surgical intervention performed and outcome in terms of morbidity and mortality of the patients included in the study group. Methods: This study was carried out at Lok Nayak Hospital and Maulana Azad Medical College, New Delhi, a tertiary care hospital between November 2011 to March 2015. It was a retrospective study in which the records of the patients operated upon in the emergency department as peritonitis or acute intestinal obstruction and whose diagnosis was later confirmed as tuberculosis on histopathology were analysed with regards clinic-pathologic profile, intra-operative findings, surgical intervention performed and outcome in terms of morbidity and mortality. Results: The mean age of our study group was 28.7 years. 70% of our patients were found to be in the underweight category and 30% were in the normal category. Fourty three (56.6%) presented to the hospital with features suggestive of peritonitis and thirty-three (43.4) were suffering from acute intestinal obstruction. The commonest intra-operative finding encountered was ileal perforation followed by multiple small bowel perforations, solitary stricture of the small bowel with perforation, ileo-cecal mass, adhesions or bands, single or multiple strictures, stricture with impending small bowel perforation and jejunal perforation. The frequently performed surgical procedures were ilesotomy, resection and anastamosis of the involved bowel, primary repair of thr perforation, right hemicolectomy, adhesiolysis, stricturoplasty (done in case of single stricture, mostly), jejunostomy and peritoneal and omental biopsy. Conclusions: Tuberculosis is a very grave disease, studies with larger number of patients need to be conducted to standardise its surgical management as at present there is no standardised surgical management protocol.